Comparison of success rate of nifedipine, progesterone, and bed rest for inhibiting uterine contraction in threatened preterm labor - Saifon Chawanpaiboon (2018)
Aim: To compare the success rates and gestational ages at delivery of nifedipine, proluton depot administration as a tocolytic agent and bed rest groups to pregnant women with threatened preterm labor. Material and Methods: A total of 150 pregnant women with threatened preterm labor between 28 and 35 weeks of gestation were enrolled in the study. All women underwent contraction inhibition randomly sorted into three groups. The first and second groups were inhibited with nifedipine and proluton depot, respectively. The third group was admitted for bed rest. Results: Nifedipine, proluton depot and bed rest can be used to inhibit contraction in threatened preterm labor. However, when time-to-event test was used, nifedipine took the shortest time for contraction inhibition with statistical significance. Conclusion: Nifedipine, proluton depot and bed rest can be used successfully to inhibit contraction in threatened preterm labor. However, nifedipine took the shortest time to inhibit uterine contraction in threatened preterm labor. © 2011 The Authors.